The Curse of Cash : How Large-Denomination Bills Aid Crime and Tax Evasion and Constrain Monetary Policy - Rogoff, Kenneth S. (Book collections on Project MUSE., 2017)
The world is drowning in cash--and it's making us poorer and less safe. In The Curse of Cash, Kenneth Rogoff, one of the world's leading economists, makes a persuasive and fascinating case for an idea that until recently would have seemed outlandish: getting rid of most paper money.--Amazon.com.